Flexible thin film pH sensor based on low‐temperature atomic layer deposition. Issue 7 (31st May 2017) - Jakob, Markus H.; Gutsch, Sebastian; Chatelle, Claire; Krishnaraja, Abinaya; Fahlteich, John; Weber, Wilfried; Zacharias, Margit
Abstract : Flexible and transparent zinc oxide (ZnO) thin film field‐effect transistors (TF‐FET) for the use as small volume potentiometric pH sensors are developed. Low temperature atomic layer deposition (ALD) is used for the fabrication of the metal oxides ZnO and aluminum dioxide (Al2 O3 ). Changing the deposition temperature of the ZnO from 150 to 100 °C allowed a significant increase in resistivity by four orders of magnitude. Hence, adjusting the controlled low carrier concentration for the field‐effect based sensor is demonstrated. ZnO TF‐FET pH sensors fabricated on silicon/silicon dioxide (Si/SiO2 ) substrates are compared with sensors based on flexible and transparent polyethylene naphthalate (PEN) foil substrates. Comparison of both types of pH sensors showed successful pH sensitivity for pH ranging from 5 to 10 in both cases. Abstract : In this work, Jakob et al. present a zinc oxide thin film field‐effect transistor (ZnO TF‐FET) on flexible and transparent polyethylene naphthalate (PEN) foils, applicable for mass production. The potentiometric pH sensor was integrated in a microfluidic (flow‐thru) device, allowing the analysis of electrolyte solutions in the small tens of microliter range. The sensor response was close to the Nernstian limit.